2013
DOI: 10.1002/anie.201304298
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phosphoric Acid Directed Regioselective Acetalization of Carbohydrate‐Derived 1,2‐Diols

Abstract: In control: A chiral phosphoric acid catalyst significantly enhances or completely overrides the inherent regioselective acetalization profiles exhibited by monosaccharide-derived 1,2-diol substrates. This study represents the first example of chiral-catalyst-directed regio- and enantioselective intermolecular acetalizations, which are complementary to existing methods for substrate-controlled functionalization of polyols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Intrigued by the unique regioselectivity toward secondary alcohol observed with IP R , we decided to take a closer look on this phenomenon ( Scheme 2a ). 6b , 17 , 18 Such a transformation is in contrast to the studies conducted by Taylor et al , in which the borinic acid exclusively functionalized the primary alcohol of a terminal diol. 4 b It was thus surmised that the judicious choice of an ammonium salt would reveal a novel, catalytic regioselective alkylation of the secondary alcohol of terminal vicinal diols.…”
Section: Resultsmentioning
confidence: 67%
“…Intrigued by the unique regioselectivity toward secondary alcohol observed with IP R , we decided to take a closer look on this phenomenon ( Scheme 2a ). 6b , 17 , 18 Such a transformation is in contrast to the studies conducted by Taylor et al , in which the borinic acid exclusively functionalized the primary alcohol of a terminal diol. 4 b It was thus surmised that the judicious choice of an ammonium salt would reveal a novel, catalytic regioselective alkylation of the secondary alcohol of terminal vicinal diols.…”
Section: Resultsmentioning
confidence: 67%
“…1 ), the chemoselective or regioselective derivatization of a single functional group in a multifunctional substrate becomes a significant question to address. 12 As entropic factors govern the intramolecular glycosylation, the chemoselectivity of the initial attachment of the sugar silane to a single functional group introduces a strategy for site-selective glycosylation of complex multifunctional substrates. Since both ketones and alcohols are competent substrates for the catalytic addition of sugar silanes, chemo- and regioselective additions to both hydroxyketones and to diols would provide important advances towards site-selective glycosylation.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has a long‐standing interest in the application of chiral phosphoric acids (CPAs) to control the regio‐ and stereoselective functionalization of natural products . In our recent efforts, we demonstrated that CPAs could mimic enzymatic processes and control the regioselectivity and/or stereoselectivity of acetalization, spiroketalization, and glycosylation reactions. Inspired by the endo regiocontrol exhibited by the epoxide hydrolase Lsd19, which catalyzes the selective formation of lasalocid A rather than its kinetically favored regioisomer isolacid A (Figure B), we sought to investigate the possibility of controlling the formation of the exo and endo products through CPA catalysis.…”
Section: Introductionmentioning
confidence: 99%